Pernikahan Parak Pada Masyarakat Gayo Dalam Kajian Hukum Islam - R, Rahmayanti; Saifullah, T; H, Hamdani; Alfikri, Albert; M, Munardi; Nur, Mukhlish M (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The marriage system in Gayo, especially in the Hakim community of Lut Tawar District, strictly prohibits marriage with the same village of origin. This is a provision from ancient ancestors who lived in groups and lived in the same area because the group still had sibling relationships. Then to avoid quarrels between kuru, a rule was made that prohibited marriage within one kuru. This is considered an ancestral vow. This marriage only prohibits marriage to the guardian's hometown (father). If there is a violation of this custom, then the mistake that can be punished in the form of parak by slaughtering a buffalo and giving rice and cooking utensils given to the community as village cleaners. This study aims to find out how the parak marriage custom in Central Aceh and the consequences of the parak marriage custom law in Lut Tawar District, Central Aceh District. The research method used is empirical juridical by collecting data from the field. Then the research approach used qualitatively will reveal the social meaning of the phenomena that will be obtained from the respondents. Furthermore, the nature of this research is descriptive qualitative by describing and answering in detail the problems to be studied. Based on the results of the study it is known that the custom of parak marriage does not prohibit same-tribe marriages. However, it is forbidden to marry one kuru (group) that has existed since ancient times. Then parak happened because of relatives who were caused by the marriage of agon, juelen so they moved around the village and now Kosu's marriage always remembers the hometown of the guardian. In Islamic law, marriage is also prohibited because one lineage is an arrangement and result of a marriage relationship. The author can conclude that the custom of parak marriage is not against Islamic law. It was suggested to Reje (village head), traditional leaders, and community leaders and other parties to carry out a movement in the form of an annual visit to the kuru to strengthen adat because currently there is a lot of mixing of tribes from all over.